2020
DOI: 10.31462/jcemi.2020.02085100
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of labor productivity for building projects in Pakistan

Abstract: This study attempts to unveil and prioritize the factors affecting labor productivity in Pakistani construction industry. A triangulation strategy was adopted, comprised of a comprehensive literature review, data collection through a questionnaire survey from contractors, clients and consultants, and Delphi survey. Fortyone labor productivity factors, shortlisted through literature review, were ranked by 315 respondents based on their past experience. The relative importance index was calculated to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…According to Fox and Skitmore [10] and Low, Abdul-Rahman [11], some of the factors influencing the development of the construction industry are: long-term vision and policy, basic physical and institutional infrastructure, thinking and implementing the best (a best practice and learning culture), financial and human resources, and, techniques assisting high production performance. Similarly, aspects such as time and cost overruns [12,13], quality and associated management of constructed facilities using innovative tools such as six sigma [14], management of larger infrastructure projects such as public-private partnership based endeavors [15], and labor productivity and associated assessments [16][17][18] are some other issues faced by the global construction industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Fox and Skitmore [10] and Low, Abdul-Rahman [11], some of the factors influencing the development of the construction industry are: long-term vision and policy, basic physical and institutional infrastructure, thinking and implementing the best (a best practice and learning culture), financial and human resources, and, techniques assisting high production performance. Similarly, aspects such as time and cost overruns [12,13], quality and associated management of constructed facilities using innovative tools such as six sigma [14], management of larger infrastructure projects such as public-private partnership based endeavors [15], and labor productivity and associated assessments [16][17][18] are some other issues faced by the global construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…The construction industry of Pakistan has experienced many ups and downs over the past few decades with many problems and challenges confronting it. These include poor site safety record, unsatisfactory environmental performance, vast use of traditional and labor-intensive construction methods, incompetent workforce, short-term attitude to business development, and, fragmentation and adversarial culture within the industry [18,[27][28][29]. Sheikh, Ullah [16] emphasize labor productivity and associated poor workmanship as one of the key barriers to the progress of the local construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these issues, contractors should implement technical procedures to improve construction labor productivity. Likewise, [9,10] stated that it is challenging to improve productivity without improved work methods. Productivity is the most important goal.…”
Section: Introductionmentioning
confidence: 99%
“…Since the identification of factors that influence construction productivity is essential for productivity performance improvement, different studies identified numerous factors that affect CLP [12]. Several studies used questionnaire surveys to identify factors with the greatest influence on CLP [13][14][15][16][17][18][19]. However, many studies notably focused on finding CLP factors, and few works are found in the literature on labor productivity prediction [20].…”
Section: Introductionmentioning
confidence: 99%